2013
DOI: 10.7475/kjan.2013.25.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Physicians and Nurses' Attitudes toward Family Presence during Cardiopulmonary Resuscitation

Abstract: Purpose:The purpose of this study was to compare the attitude of physicians and nurses toward family presence during cardiopulmonary resuscitation (CPR). Methods: 100 physicians and 100 nurses from five hospitals with than 500 beds in B city were surveyed using a Family Presence During Resuscitation (FPDR) Inventory. The data were analyzed by t-test, ANOVA and Duncan's multiple range test using SPSS/WIN 19.0 version. Results: Nurses showed more positive attitudes toward family presence during CPR but reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 10 publications
1
7
0
1
Order By: Relevance
“…While this was higher than that found among physicians (2.874) and nurses (2.88) in a Taiwanese study that used the same instrument (Lai et al, 2017), it was similar to the results for physicians (3.41) and nurses (3.30) found in another Korean study (Cha, 2018). Further, only 41.3% of the participants in our study had experienced FPDR, which is a low rate, similar to that reported by a previous study (Cho et al, 2013). Another study, which reported that 48% of 124 ICU nurses with abundant CPR experience never advised families to be present during resuscitation and that 45% had only invited families 1–5 times, confirms that FPDR is primarily determined by healthcare providers (Powers & Candela, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…While this was higher than that found among physicians (2.874) and nurses (2.88) in a Taiwanese study that used the same instrument (Lai et al, 2017), it was similar to the results for physicians (3.41) and nurses (3.30) found in another Korean study (Cha, 2018). Further, only 41.3% of the participants in our study had experienced FPDR, which is a low rate, similar to that reported by a previous study (Cho et al, 2013). Another study, which reported that 48% of 124 ICU nurses with abundant CPR experience never advised families to be present during resuscitation and that 45% had only invited families 1–5 times, confirms that FPDR is primarily determined by healthcare providers (Powers & Candela, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…(23) However, in South Korea, researchers have suggested developing and implementing an educational program to modify the negative perception of professionals about the presence of families in ER. (24) These studies, therefore, show that changes in the formative process collaborate to diminish the symbolic culture of professional exclusion.…”
Section: Discussionmentioning
confidence: 98%
“…또한, 심폐소생술 시 가 족입회가 원활히 이루어질 수 있도록 심폐소생술 시 가족입회에 대한 가이드라인이 제시되고 있다 [1,11,12]. 국내에서도 보호자 로부터 심폐소생술 시 가족입회를 요청받는 의료인들이 점차 많 아지고 있긴 하지만 [13,14]…”
unclassified